Combination of QSAR, molecular docking, molecular dynamic simulation and MM-PBSA: analogues of lopinavir and favipiravir as potential drug candidates against COVID-19. Issue 8 (24th May 2022) - Rafi, Md. Oliullah; Bhattacharje, Gourab; Al-Khafaji, Khattab; Taskin-Tok, Tugba; Alfasane, Md. Almujaddade; Das, Amit Kumar; Parvez, Md. Anowar Khasru; Rahman, Md. Shahedur
Abstract: Pandemic COVID-19 infections have spread throughout the world. There is no effective treatment against this disease. Viral RNA-dependent RNA polymerase (RdRp) catalyzes the replication of RNA from RNA and the main protease (M pro ) has a role in the processing of polyproteins that are translated from the RNA of SARS-CoV-2, and thus these two enzymes are strong candidates for targeting by anti-viral drugs. Small molecules such as lopinavir and favipiravir significantly inhibit the activity of M pro and RdRp in vitro . Studies have shown that structurally modified lopinavir, favipiravir, and other similar compounds can inhibit COVID-19 main protease (M pro ) and RNA-dependent RNA polymerase (RdRp). In this study, lopinavir and its structurally similar compounds were chosen to bind the main protease, and favipiravir was chosen to target RNA-dependent RNA polymerase. Molecular docking and the quantitative structure-activity relationships (QSAR) study revealed that the selected candidates have favorable binding affinity but less druggable properties. To improve the druggability, four structural analogues of lopinavir and one structural analogue of favipiravir was designed by structural modification. Molecular interaction analyses have displayed that lopinavir and favipiravir analogues interact with the active site residues of M pro and RdRp, respectively. Absorption, distribution, metabolism, excretion and toxicity (ADMET) properties, medicinal chemistry profile, and physicochemical features were shown that all structurally modified analogues are less toxic and contain high druggable properties than the selected candidates. Subsequently, 50 ns molecular dynamics simulation of the top four docked complexes demonstrated that CID44271905, a lopinavir analogue, forms the most stable complex with the M pro . Further MMPBSA analyses using the MD trajectories also confirmed the higher binding affinity of CID44271905 towards M pro . In summary, this study demonstrates a new way to identify leads for novel anti-viral drugs against COVID-19. Communicated by Ramaswamy H. Sarma